Management of Attention-Deficit/Hyperactivity Disorder by Developmental-Behavioral Pediatricians: A DBPNet Study. Issue 7 (September 2016) - Harstad, Elizabeth; Blum, Nathan; Gahman, Amy; Shults, Justine; Chan, Eugenia; Barbaresi, William
Abstract: Objective: To describe practice patterns for developmental-behavioral pediatricians (DBPs) practicing within Developmental-Behavioral Pediatrics Research Network (DBPNet) academic medical centers providing follow-up for children with attention-deficit/hyperactivity disorder (ADHD) and determine how well they adhere to American Academy of Pediatrics ADHD Clinical Practice Guidelines. Methods: Seventy-eight DBPs at 12 academic medical centers participating in the DBPNet were asked to complete follow-up encounter surveys for patients with ADHD or autism spectrum disorder seen from 12/2011 through 6/2012. Data regarding patient characteristics, comorbid conditions, and medication management were obtained at the time of each visit. Results: Fifty-seven DBPs completed 301 ADHD follow-up encounter surveys; 75.3% of patients were male with mean age 9.57 years (SD = 3.3). Race/ethnicity was primarily white/non-Hispanic with similar numbers on private insurance (41.5%) versus Medicaid (45.5%). DBPs identified comorbid learning disorders in 27.6% of children ≥6 years. Only 58.3% of children <6 years received counseling/behavioral therapy or had it recommended during the visit. DBPs primarily (90.6%) prescribed medications FDA-approved for ADHD treatment and growth was monitored for >98% of visits during which stimulants were prescribed. Parent- and teacher-completed rating scales were reviewed/completed during 43.9% and 37.8% of visits, respectively. There were no child or physician factors consistently associated with variation in practice patterns. Conclusion: Developmental-behavioral pediatricians practicing within DBPNet medical centers adhere to the recommended medication prescribing practices for ADHD, including use of FDA-approved medications and monitoring growth. However, DBPs within DBPNet do not consistently review ADHD rating scales or recommend behavioral counseling for children <6 years of age as recommended.